Characterization of microstructures of SAN foam core using micro-computed tomography. Issue 4 (July 2021) - Chen, Youming; Das, Raj; Wang, Hui; Battley, Mark
In this study, the microstructure of a SAN foam was imaged using a micro-CT scanner. Through image processing and analysis, variations in density, cell wall thickness and cell size in the foam were quantitatively explored. It is found that cells in the foam are not elongated in the thickness (or rise) direction of foam sheets, but rather equiaxed. Cell walls in the foam are significantly straight. Density, cell size and cell wall thickness all vary along the thickness direction of foam sheets. The low density in the vicinity of one face of foam sheets leads to low compressive stiffness and strength, resulting in the strain localization observed in our previous compressive tests. For M80, large open cells on the top face of foam sheets are likely to buckle in compressive tests, therefore being another potential contributor to the strain localization as well. The average cell wall thickness measured from 2D slice images is around 1.4 times that measured from 3D images, and the average cell size measured from 2D slice images is about 13.8% smaller than that measured from 3D images. The dispersions of cell wall thickness measured from 2D slice images are 1.16–1.20 times those measured from 3D images. The dispersions of cell size measured from 2D slice images are 1.12–1.36 times those measured from 3D images.